Improved Performances of a Fluidized Bed Photoreactor by a Microscale Illumination System - Paolo Ciambelli; Diana Sannino; Vincenzo Palma; Vincenzo Vaiano; Roberto S. Mazzei (International Journal of Photoenergy)
The performances of a gas-solid two-dimensional fluidized bed reactor in photocatalytic selective oxidation reactions, irradiated with traditional UV lamps or with a microscale illumination system based on UV emitting diodes (UVA-LEDs), have been compared. In the photocatalytic oxidative dehydrogenation of cyclohexane to benzene on MoOx/TiO2-A12O3 catalyst the use of UVA-LEDs modules allowed to achieve a cyclohexane conversion and benzene yield higher than those obtained with traditional UV lamps. The better performances with UVA-LEDs are due to the UVA-LEDs small dimensions and small-angle emittance, which allow photons beam be directed towards the photoreactor windows, reducing the dispersion outside of photoreactor or the optical path length. As a consequence, the effectively illuminated mass of catalyst is greater. We have found that this illumination system is efficient for photo-oxidative dehydrogenation of cyclohexane to cyclohexene on sulphated MoOx/𝛾-A12O3 and ethanol to acetaldehyde on VOx/TiO2.